Environmental Impacts and Behavioral Adaptations of Honeybees in Algeria: A Review of Apis mellifera intermissa and Apis mellifera sahariensis Characteristics - Yamina Haider; Noureddine Adjlane; Nizar Haddad (Insects, 2025)
Honeybees are vital for pollination and the overall health of ecosystems. Since the 18th century, the intricate biology of honeybees has been a subject of scientific inquiry. Understanding their biological and behavioral characteristics is essential for effective beekeeping, honey production, and ecosystem sustainability. This review examines the environmental impact and management practices on the health of local honeybees in Algeria, focusing on Apis mellifera intermissa and Apis mellifera sahariensis. We summarize research findings on genetic diversity, morphometric traits, behavioral characteristics, and adaptation of local honeybees. Additionally, we discuss the threats posed by abiotic and biotic stressors and highlight the importance of conservation and sustainable management. The reviewed studies indicate that environmental factors significantly influence the behavioral characteristics and adaptation of local honeybees. Notably, the hygienic behavior of A. m. intermissa contributes to their resistance against diseases and the Varroa destructor mite. Further research in these areas is important for enhancing our understanding of honeybee health and population dynamics in Algeria, thereby informing strategies for sustainable beekeeping practices.